Study of immediate release spherical microparticles containing clarithromycin using a hot-melt fluid bed technique - Homar, Miha (Acta chimica slovenica, 2011)
The aim of the study was to evaluate a hot-melt technique for preparation of immediate release spherical microparticles containing clarithromycin with acceptable characteristics and process yield. A modified fluid bed apparatus with rotor insert was used to prepare spherical microparticles in the size range of 125-355 im. Poloxamer 188, PEG-32 glyceryl laurate (Gelucire 44/14) and a mixture of polyethylene glycol (PEG) 4000 with PEG 400 were used as meltable binders. Key process parameters were identified and optimized and their influence on process yield and microparticles characteristics was determined. Microparticles with poloxamer 188 and PEG exhibited relatively good mechanical properties. Process yield was around 70% and 60% in the case of PEG and poloxamer 188 respectively. Microparticles prepared with PEG-32 glyceryl laurate exhibited poor mechanical properties and process yield compared to other microparticles. The process was shown to be limited by the bed temperature, exhibiting the best process stability with poloxamer 188 followed by PEG and PEG-32 glyceryl laurate. Dissolution rate and equilibrium concentration of clarithromycin released from prepared microparticles was improved compared to similar particles prepared by wet granulation.
Keywords: farmacevtske oblike; klaritromicin; polietilen glikol; sferični mikrodelci; sproščanje učinkovin